SOCIO-ECONOMIC STATUS AND SELF EFFICACY WITH STUDENTS' PSYCHOLOGICAL WELL-BEING IN JUNIOR HIGH SCHOOL - Sabrina Rahayu; Abdul Munir; Nina Siti Salmaniah Siregar (RADJA PUBLIKA, 2025)
This study aims to analyze the relationship between socioeconomic status and self-efficacy on the psychological well-being of junior high school students. The background of this study is based on the importance of psychological well-being in adolescent development, which is influenced by external factors such as family socioeconomic conditions and internal factors such as individual self-confidence. This study uses a quantitative correlational approach with a cross-sectional survey design. The sample consisted of 181 eighth grade students at SMP Negeri 1 Banda Aceh City who were selected using stratified random sampling. The instruments used included a socioeconomic status questionnaire, a self-efficacy scale, and a psychological well-being scale. The results of the analysis showed that socioeconomic status and self-efficacy simultaneously had a significant effect on students' psychological well-being (F = 32.90; p < 0.05). The R² value of 0.270 indicates that 27% of the variance in psychological well-being can be explained by these two variables. This finding indicates that both environmental factors and students' self-confidence play an important role in shaping psychological well-being. The practical implication of this study is the need for support from schools and parents in improving students' psychological well-being through interventions based on strengthening self-efficacy and improving socio-economic conditions. This study contributes to the literature on educational psychology in Indonesia, particularly in the context of junior secondary education.